Understanding religious behavior - Levin, S. (Journal of religion and health, 1979)
The attached (to mother) fetus-infant finds his religious expression in Buddhism. The attached (to group) juvenile finds his religious expression in Judaism and other tribalisms. The attached (to spouse) adult finds his religious expression in agnosticism and secularism. Attached phases are placid and of progressively decreasing emotional intensity. The three detaching phases are hurtful and hence soteriological, and are also of progressively decreasing emotional intensity. The toddler-young child finds his religious expression in Christianity, the adolescent in atheism and/or Marxism, and the aged, sick or dying plucks at any religious or secular aid.